2001
DOI: 10.4049/jimmunol.166.4.2658
|View full text |Cite
|
Sign up to set email alerts
|

A Role for IFN-αβ in Virus Infection-Induced Sensitization to Endotoxin

Abstract: Underlying viral infections can heighten sensitivity and worsen cytokine-mediated disease following secondary inflammatory challenges. Mechanisms for this are poorly understood. The impact of the innate response to lymphocytic choriomeningitis virus (LCMV) infection on sensitivity to endotoxin (LPS) was investigated. Compared with uninfected mice, infection with LCMV for 2-days-sensitized mice to LPS by ∼2-fold for lethality and by 2- to 6-fold for serum TNF-α levels. Priming for LPS-induced TNF-α was also see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
70
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 45 publications
(34 reference statements)
1
70
1
Order By: Relevance
“…Indeed, virus-induced production of chemokines is known to be important for T-cell migration into peripheral tissues and efficient antigen clearance 15 , and chemokine production in pancreatic islets has been shown to have a role in T-cell infiltration into this organ 16 . Tolllike receptor (TLR) signaling following recognition of distinct pathogen patterns can also influence the production of proinflammatory cytokines and chemokines by DCs and macrophages [17][18][19][20][21] . Eleven different TLRs have been identified so far 22 , and these recognize molecular patterns such as RNA (receptors TLR3, TLR7 and TLR8) 23,24 , DNA (TLR9) 25 or l ipopolysaccharide (TLR4) 26 .…”
mentioning
confidence: 99%
“…Indeed, virus-induced production of chemokines is known to be important for T-cell migration into peripheral tissues and efficient antigen clearance 15 , and chemokine production in pancreatic islets has been shown to have a role in T-cell infiltration into this organ 16 . Tolllike receptor (TLR) signaling following recognition of distinct pathogen patterns can also influence the production of proinflammatory cytokines and chemokines by DCs and macrophages [17][18][19][20][21] . Eleven different TLRs have been identified so far 22 , and these recognize molecular patterns such as RNA (receptors TLR3, TLR7 and TLR8) 23,24 , DNA (TLR9) 25 or l ipopolysaccharide (TLR4) 26 .…”
mentioning
confidence: 99%
“…It was purified and had no detectable endotoxin, i.e., LPS, using standard assays. However, because previous work from our laboratory has demonstrated that sensitivity to endotoxin can be increased 10-to 100-fold during viral infections (37,38), and because treatment of both mutated and functional sIL-15R␣ had stimulatory effects on NK cells in C57BL/6 mice, experiments with this reagent were performed in the endotoxin-resistant C3H/ HeJ mice. Under these conditions, this very specific blocker of IL-15 functions inhibited the accumulation of NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…First, Schiavoni et al (19) have recently reported elevated expression of type I IFNs in the spleen of normal mice at 6 h after CY administration (the earliest time point studied), which was associated with subsequent elevation in biological activity of type I IFNs in the sera of the CY-treated mice. Second, type I IFNs were reported to favor the development of a type 1 cytokine response in nontumor systems (20 -23) and to prime mice for elevated production of TNF-␣ in response to LPS (24). As a representative of the type I IFNs, we decided to focus our attention on IFN-␤ and not IFN-␣ because there is a single IFN-␤, whereas there are multiple subtypes of IFN-␣ (25).…”
mentioning
confidence: 99%